2020
DOI: 10.3390/ma13214731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrated Lime on Indirect Tensile Stiffness Modulus of Asphalt Concrete Produced in Half-Warm Mix Technology

Abstract: Half-warm mix asphalt (HWMA) mixtures can be produced at temperatures ranging from 100 °C to 130 °C, depending on the production methods used. The lowest mixing temperature can be achieved by using water-foamed bitumen. The mixture should be characterized by a long service life, defined by the resistance to permanent deformation and high stiffness modulus at temperatures above zero. It is therefore important to ensure the adequately high quality of the bitumen binder. Bitumen 50/70 was provided with appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A life cycle cost analysis [ 3 ] showed that HL addition saved approximately 20$ per ton on asphalt concrete, whilst increasing the expected service life of the constructed pavement by 38%. Extensive research has reported the results of the stiffening effect of HL on asphalt mixes [ 4 , 5 , 6 ] and improvement in fracture-, aging-, and moisture-resistance of asphalt concretes with HL. addition [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A life cycle cost analysis [ 3 ] showed that HL addition saved approximately 20$ per ton on asphalt concrete, whilst increasing the expected service life of the constructed pavement by 38%. Extensive research has reported the results of the stiffening effect of HL on asphalt mixes [ 4 , 5 , 6 ] and improvement in fracture-, aging-, and moisture-resistance of asphalt concretes with HL. addition [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of considerable research on HL-modified asphalt concrete, traditional research has primarily focused on the interest in mechanical properties under different temperature and environmental exposure conditions to identify the optimum rate of HL addition [2][3][4]. For example, a recent durability investigation on a pavement having five years of service showed that HL addition increased the resistance to moisture damage, but the differences between 0.5 and 1.5% HL addition were very limited [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bitumen ageing in conventional mixtures is not as important as in HWMA and WMA intended for pavement upper layers [ 13 , 14 , 30 , 36 , 37 ]. The use of foamed bitumen reduces the short-term ageing process to a very short period during its injection into the mineral mix at <100 °C.…”
Section: Introductionmentioning
confidence: 99%